Association of Gait Characteristics and Depression in Patients with Parkinson’s Disease Assessed in Goal-Directed Locomotion Task - Péter Kincses; Norbert Kovács; Kázmér Karádi; Ádám Feldmann; Krisztina Dorn; Zsuzsanna Aschermann; Sámuel Komoly; Tibor Szolcsányi; Árpád Csathó; János Kállai (Parkinson's Disease)
Introduction. In the genesis of Parkinson’s disease (PD) clinical phenomenology the exact nature of the association between bradykinesia and affective variables is unclear. In the present study, we analyzed the gait characteristics and level of depression in PD and healthy volunteers. Methods. Patients with PD (n=48) and healthy controls (n=52) were recruited for the present study. Walking speed, stride length, and cadence were compared between groups while participants completed a goal-directed locomotion task under visually controlled (VC) and visually noncontrolled conditions (VnC). Results. Significantly higher depression scores were found in PD comparing to healthy control groups. In PD, depression was associated with gait components in the VC wherein the place of the target was visible. In contrast, in healthy subjects the depression was associated with gait components in VnC wherein the location and image of the target were memorized and recalled. In patients with PD and depression, the visually deprived multitask augments the rate of cadence and diminishes stride length, while velocity remains relatively unchanged. The depression associated with gait characteristics as a comorbid affective factor in PD, and that impairs the coherence of gait pattern. Conclusion. The relationship between depression and gait parameters appears to indicate that PD not only is a neurological disease but also incorporates affective disturbances that associate with the regulation of gait characteristics.